WE ARE NOT ECONOMIC SCAVENGERS, BUT MIGRANT STUDENTS: TRUE LIVE EXPERIENCE OF AFRICAN MIGRANT STUDENTS IN EUROPE - Akpan, Louis Okon; Ohadiugha, Marian N. (Journal of Continuing and Development Education, 2024)
Millions of African migrant students have crossed and continue to cross the Mediterranean Sea yearly to Europe in search for better source of livelihood and foreign degrees. The migration of Africans to Europe, therefore, had made the hosts to be apprehensive and hostile towards the migrants. Based on the foregoing, the study explored the true-life story of African migrant students in Europe. Two research questions were formulated to guide the study. Qualitative approached was adopted, interpretive paradigm used to make sense of the migrants’ narrative. Purposive sampling technique was deployed to select eleven European countries. Twenty-two migrant students were used to gather the information for the study. In line with qualitative approach adopted, narrative analysis was used to analyse the information narrated by the migrant students. Findings indicated that aside from the fact that the majority of African migrant students were segregated in all sphere of life, they also bullied emotionally. Furthermore, African migrant students were treated the way they were treated based on the allegation that they were criminals and economic scavengers.